2011
DOI: 10.1039/c0jm03613g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis–structure–performance correlation for polyaniline–Me–C non-precious metal cathode catalysts for oxygen reduction in fuel cells

Abstract: In this report, we present the systematic preparation of active and durable non-precious metal catalysts (NPMCs) for the oxygen reduction reaction in polymer electrolyte fuel cells (PEFCs) based on the heat treatment of polyaniline/metal/carbon precursors. Variation of the synthesis steps, heat-treatment temperature, metal loading, and the metal type in the synthesis leads to markedly different catalyst activity, speciation, and morphology. Microscopy studies demonstrate notable differences in the carbon struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
503
5
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 562 publications
(553 citation statements)
references
References 74 publications
30
503
5
6
Order By: Relevance
“…The sample treated at 1000°C showed the highest activity in both acidic and alkaline electrolytes. Although previous studies have reported production of nitrogen-doped carbon catalysts with tunable physical and chemical properties, 35,36 here we provide the first demonstration that the diameter of carbon tubes can be manipulated by varying the TM used in the precursor mixture. Given the important role played by the TM in controlling nanocarbon morphology, we anticipate similarly strong effect on the catalytic properties of these nanocarbons.…”
Section: Controlled Morphologies and Structuresmentioning
confidence: 91%
“…The sample treated at 1000°C showed the highest activity in both acidic and alkaline electrolytes. Although previous studies have reported production of nitrogen-doped carbon catalysts with tunable physical and chemical properties, 35,36 here we provide the first demonstration that the diameter of carbon tubes can be manipulated by varying the TM used in the precursor mixture. Given the important role played by the TM in controlling nanocarbon morphology, we anticipate similarly strong effect on the catalytic properties of these nanocarbons.…”
Section: Controlled Morphologies and Structuresmentioning
confidence: 91%
“…8 The peak at a binding energy of 398.7 eV should also include a contribution from nitrogen bound to the metal (Me-N), due to the small difference between binding energies of N-Me and pyridinic N. 8b,9 Pyridinic N (probably including Me-N) and graphitic N are generally believed to participate in the active sites. 2d,8b, [9][10] Although there was a significant amount of cobalt species (1.3-1.4 at%) in the templated C-N-Co catalysts, as indicated by XPS analysis (Table S1), we hardly observed any metal-containing nanoparticles by TEM inspection because the etching agent (hydrogen fluoride) dissolves both the inorganic templates and metal/metal oxide nanoparticles. 11 Xray diffraction (XRD) pattern further proved the absence of crystalline metal/metal oxide phases ( Figure S8).…”
Section: Supporting Information Placeholdermentioning
confidence: 97%
“…This is well above the optimum content for Me-N-C catalyst precursors before pyrolysis, typically below 2-3 wt. % [7,[14][15][16]. Too large Fe or Co contents lead to the formation of highly graphitized carbon structures during pyrolysis [13,17].…”
Section: Introductionmentioning
confidence: 99%